The Impact of Serial Image Media on Dyslexia Disorder in Elementary School Mathematics Learning - Reflina Sinaga; Ester Julinda Simarmata (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to analyze the development of serial image media for students who experience dyslexia disorder in elementary schools in Medan Kota sub-district and to determine the effectiveness of the development of serial image media for students experiencing dyslexia disorder in elementary schools in Medan Kota district. This research method is to use the research and development method (Research and Developmental), which is a process used to develop and validate products. The location of this research was carried out in elementary schools in Medan Kota District, North Sumatera. The conclusions in this study are the development of image media on dyscalculia in primary schools to be developed and applied for students who have difficulty counting.